The impact of monetary policy on income inequality in Indonesia - Silva, Livia Nadhira; Utama, Chandra; Mokoginta, Ivantia Savitri (Universitas Muhammadiyah Yogyakarta, 2025)
This study examines the influence of monetary policy on income inequality in Indonesia, as measured by the Gini coefficient, across both the financial and real sectors. The study employed a Structural Vector Autoregression (SVAR) model using semi-annual data from 34 provinces spanning the period from 2011 to 2022. This study emphasizes the influence of monetary policy on income inequality through the income channel, wherein families that own financial assets benefit from implementing contractionary monetary policy, while wage-dependent households experience no impact. The results indicate that expansionary monetary policy reduces income inequality, while contractionary monetary policy exacerbates it. This research suggests that a monetary policy conducive to economic development should be implemented with low interest rates. Low interest rates may mitigate income inequality in Indonesia.